2014
DOI: 10.1074/jbc.m114.576819
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Curcumin with Either Gramicidin or Ouabain Selectively Kills Cells That Express the Multidrug Resistance-linked ABCG2 Transporter

Abstract: Background:The ABCG2 transporter is an ATP-dependent efflux pump that contributes to multidrug resistance. Results: Curcumin in combination with gramicidin or ouabain reduces intracellular ATP levels in ABCG2-expressing cells and selectively kills these cells over parental cells. Conclusion: ABCG2-expressing cells display collateral sensitivity toward these combinations of compounds. Significance: Understanding ABCG2-mediated collateral sensitivity is helpful in finding ways to combat multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In addition, curcumin also could inhibit the expression of MRP1 in a concentration dependent manner in Y79 cells . Besides, it was reported that curcumin inhibited drug efflux and increased the efficacy of many anticancer agents in multidrug‐resistant cancers . Moreover, curcumin and demethoxycurcumin could inhibit P‐gp but BDMC may modulate the function of other efflux transporters such as MRPs .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, curcumin also could inhibit the expression of MRP1 in a concentration dependent manner in Y79 cells . Besides, it was reported that curcumin inhibited drug efflux and increased the efficacy of many anticancer agents in multidrug‐resistant cancers . Moreover, curcumin and demethoxycurcumin could inhibit P‐gp but BDMC may modulate the function of other efflux transporters such as MRPs .…”
Section: Discussionmentioning
confidence: 99%
“…The MTT-bioassay data unambiguously showed that the pH-sensitive liposomal formulation of curcumin proved to significantly outclass the free drug in terms of The established high efficacy of formulated curcumin in resistant cells is of special interest, since this compound has been shown to restore the responsiveness to anticancer drugs and is considered as a potential multidrug-resistance reversal agent (Li et al, 2013;Li et al, 2011;Misra and Sahoo, 2011;Rao et al, 2014;Roy and Mukherjee, 2014;Sreekanth et al, 2011;Sreenivasan et al, 2012). The apoptosis assay firmly demonstrated that liposomal curcumin is a potent inducer of apoptotic DNA-fragmentation in HL-60, in compliance to preceding reports (Alaikov et al, 2007;Liao et al, 2008;Tan et al, 2006) and especially in HL-60/CDDP cells which proved to be more sensitive to the apoptogenic effects of equieffective levels of curcumin.…”
Section: Discussionmentioning
confidence: 96%
“…The discovery of MRP1 indicates the finding of other homologs of ABC family transporters such as the other eight ABCC subfamilies, six of which have been confirmed to be involved in the exclusion of anticancer agents and antiviral compounds 19, 20. Besides P‐gp and MRP1, other MDR‐related membrane transporters (e.g., the breast cancer resistance protein BCRP, also known as ABCG2) are also important ABC transporter,21, 22, 23 which plays an essential role in resistance to a variety of cancer therapeutic agents, including mitoxantrone, topotecan, doxorubicin, and SN‐38 24. Moreover, other ABC family transporters have also been found to be associated with drug resistance, such as the “sister of P‐gp,” ABCB11, and ABCA2, although their roles in cancer multidrug resistance remain unclear 25, 26…”
Section: Mechanisms Of Cancer Multidrug Resistancementioning
confidence: 99%